Tribute to Father Dr Richard William Timm, CSC (1923- 2020): First Editor of the Bangladesh Journal Of Zoology (Bangladesh Journal of Zoology, 2021)
Abstract not availableBangladesh J. Zool. 48(2): 213-214, 2020